2020
DOI: 10.1111/spol.12590
|View full text |Cite
|
Sign up to set email alerts
|

Social capital and the impact of the recent economic crisis: Comparing the effects of economic and fiscal policy developments

Abstract: In this contribution, we offer an analysis that evaluates the impact of the recent financial and economic crisis on social capital. An economic crisis offers a unique chance to study people's associational lives, volunteering, network-making, and trust-building under duress. Theoretical perspectives on the relationship between social capital and economic development emphasize a reciprocal relationship between the two. Therefore, we hypothesize that if economic performance is compromised, this might lead to an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Moreover, we find GettingCredit significant in reducing the likelihood of borrower discouragement in the IV- 11 A positive link between the number of systemic banking crises experienced and interpersonal trust could be explained by a positive association between economic threat and pro-social tendencies, and the establishment of social support networks (Alonso-Ferres et al, 2020). Moreover, Hörisch and Obert (2020) find state action during a crisis could even lead to social capital development, which is in line with studies that find government performance influences social capital (Rothstein and Stolle, 2008).…”
Section: [Insert Table 4c]supporting
confidence: 85%
“…Moreover, we find GettingCredit significant in reducing the likelihood of borrower discouragement in the IV- 11 A positive link between the number of systemic banking crises experienced and interpersonal trust could be explained by a positive association between economic threat and pro-social tendencies, and the establishment of social support networks (Alonso-Ferres et al, 2020). Moreover, Hörisch and Obert (2020) find state action during a crisis could even lead to social capital development, which is in line with studies that find government performance influences social capital (Rothstein and Stolle, 2008).…”
Section: [Insert Table 4c]supporting
confidence: 85%
“…The finding revealed that economic growth in countries with high social capital tends to be higher than those with lower social capital. Hörisch and Obert [10] also claimed a positive association between economic crisis and social capital.…”
Section: Introductionmentioning
confidence: 98%
“…From the macroeconomic perspective, research has highlighted the impact of social capital on the economic growth [9][10][11][12]. For example, a study conducted by Muringani, Fitjar and Rodríguez-Pose [12] investigated the impact on regional economic development in 21 European countries.…”
Section: Introductionmentioning
confidence: 99%
“…This seems to have been strengthened during the crisis, as the focus has been on demand, and less on supply side measures. This demand approach further has the positive impact on social capital and reduce hardship of a financial crisis, as also shown in an article related to the last financial crisis (Hörisch & Obert, 2020), so that not only seems the policy to support employment but also that this will help in ensuring continuous cohesive societies. In this way, the crisis has not changed the overall characteristics and universality of the Nordic welfare states, but has strengthened the focus on state intervention in economies as part of how to ensure jobs and a good living standard for all citizens.…”
Section: Resultsmentioning
confidence: 83%